Effect of Du moxibustion in the treatment of Wind-phlegm disturbance vertigo (督灸疗法治疗眩晕风痰上扰证效果观察) - LUO Lihua (罗丽华); LI Silu (李思璐); LONG Yuqin (龙玉琴); YANG Yanni (杨燕妮); GENG Qingwen (耿庆文) (中西医结合护理)
Objective To investigate the effect of Du moxibustion in the treatment of Wind-phlegm disturbance vertigo. Methods Totally 164 hospitalized patients with Wind-phlegm disturbance vertigo were randomly divided into the control group and observation group, with 82 cases in each group. All patients received routine nursing during the treatment, and patients in the control group were given Du moxibustion therapy, 30 min per time, twice a week for 2 weeks. The degree of vertigo (posterior circulation ischemia) was measured before and after treatment. Results The total score of the grading scale of vertigo (posterior circulation ischemia) was decreased in both two groups after intervention, and total score in the observation group was lower than that in the control group (P＜0. 05). Conclusion The Du moxibustion is effective to relieve the clinical symptoms of patents with Wind-phlegm disturbance vertigo (目的 探讨督灸疗法治疗眩晕风痰上扰证的效果。方法 选取2022年1月—6月医院脑病科住院治疗的眩晕风痰上扰证患者164例, 采用随机数字表法分为对照组和观察组, 各82例。对照组给予常规护理, 观察组在常规护理基础上予以督灸疗法, 每次30 min, 每周2次, 治疗2周。干预后评价两组患者的中医眩晕(后循环缺血)程度分级评分表。结果 干预后两组患者眩晕症状均有改善, 但观察组中医眩晕(后循环缺血)程度分级评分表总分下降程度优于对照组, 差异有统计学意义(P＜0. 05)。结论 督灸疗法可有效改善眩晕风痰上扰证患者的眩晕程度。)